Swarm Intelligent Power-Aware Detection of Unauthorized and Compromised Nodes in MANETs. (11th December 2007) - Mehfuz, Shabana; Doja, M. N.
Abstract : Characteristics of mobile ad hoc networks (MANETs) such as lack of central coordination, mobility of hosts, and limited availability of resources make quality of service (QoS) provisioning very challenging. Limited resource availability such as battery power and insecure medium is one of the major QoS issues to be dealt with. In this paper, we have proposed a new secure power-aware ant routing algorithm (SPA-ARA) for mobile ad hoc networks that is inspired from ant colony optimization (ACO) algorithms which are a swarm intelligent technique. In this algorithm, we have introduced a new metric, next-hop availability, which is a combination of two metrics. It maximizes path availability and minimizes travel time of packets, and therefore it offers a good balance between selection of fast paths and a better use of network resources. The protocol also incorporates a trust model which helps in detection of unauthorized and compromised nodes in MANETs.